2022
DOI: 10.1097/md.0000000000028886
|View full text |Cite
|
Sign up to set email alerts
|

Academic burnout among undergraduate history students

Abstract: Background:This study aimed to examine the effect of an online psychological intervention on academic burnout of undergraduate history students in Nigeria.Method:The sample for the study consists of burned-out undergraduate history students selected randomly from public universities. A total of 18 undergraduate history students with moderate to high burnout symptoms were randomly allocated to the online intervention group, while 17 were randomly assigned to the waitlist control group.Results:The use of online … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The one-sample ttest and paired sample t-test statistics were used to analyze data concerning online REBC group participants' satisfaction with the coaching program. Post-hoc analysis for Group × Time interaction effects was carried out with Sidak in order to see which group experienced improvement on entrepreneurial attitudes just as in recent REBT intervention (Oloidi et al, 2022).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…The one-sample ttest and paired sample t-test statistics were used to analyze data concerning online REBC group participants' satisfaction with the coaching program. Post-hoc analysis for Group × Time interaction effects was carried out with Sidak in order to see which group experienced improvement on entrepreneurial attitudes just as in recent REBT intervention (Oloidi et al, 2022).…”
Section: Methods Of Data Analysismentioning
confidence: 99%
“…This perspective term can also be defined as fatigue and disengagement afflictions that the students experienced due to the prolonged subjection to the ever-increasing said school's demands [9].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is later found that the nature of the nursing field itself contributes to the students' exhaustion and stress such as long working hours, standing for long periods and packed academic schedules. This is alarming because students who experience academic burnout are likely linked to suicidal ideation Oloidi, 2022).…”
Section: Statement Of Problemmentioning
confidence: 99%